Shopping malls and neoliberal trends in Southern European cities: post-metropolitan challenges for urban planning policy - Tulumello,Simone (2016)
Whilst shopping malls have been explored at length by critical urban studies, there has been little exploration of their role in restructuring the practice of urban and spatial planning. This article uses the shopping mall as an object of study in the light of the neoliberal trends and post-metropolisation in Southern Europe, with the aim of exploring challenges for urban governance and planning practice and with a focus on the role of the ongoing economic crisis. A threefold exploratory framework - the ‘lost-in-time scenario', the ‘messianic mall model' and the ‘(im)mature planning explanation' - is used to make sense of the local versions of shopping mall development in Lisbon (Portugal) and Palermo (Southern Italy). According to findings, we highlight the clash between the multi-scalar nature of shopping malls and the dominance of the municipal scale in regulatory planning frameworks, and the risk that shopping mall development (at least in Southern Europe) may replicate uneven development patterns, reproducing the pre-conditions of the crisis without helping to overcome it.